Post-Harvest Management of Horticultural Crops - Sadhna Pandey; S.N. Pandey; P.H. Pandey (Ludhiana Kalyani)
Post- Harvest management of horticultural crops including fresh fruits, vegetables and flowers is very wide and most important.
Fruits Vegetables Flowers
Keywords: Fruits, Vegetables , Flowers